2011
DOI: 10.1038/sc.2011.19
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cycling and/or electrical stimulation on bone mineral density in children with spinal cord injury

Abstract: Study design: Randomized clinical trial. Objectives: To determine the effect of cycling and/or electrical stimulation on hip and knee bone mineral density (BMD) in children with spinal cord injury (SCI). Setting: Children's hospital specializing in pediatric SCI. Methods: A total of 30 children, aged 5-13 years, with chronic SCI were randomized to one of three interventions: functional electrical stimulation cycling (FESC), passive cycling (PC), and non-cycling, electrically stimulated exercise (ES). Each grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 24 publications
0
37
0
1
Order By: Relevance
“…[15][16][17][18][19][20] A possible reason for this conflict may be the location of measured sites, since bone mineral adaptations are limited to the bone area under mechanical stress. 33 The study by Groah et al…”
Section: The Journal Of Spinal Cord Medicinementioning
confidence: 99%
See 2 more Smart Citations
“…[15][16][17][18][19][20] A possible reason for this conflict may be the location of measured sites, since bone mineral adaptations are limited to the bone area under mechanical stress. 33 The study by Groah et al…”
Section: The Journal Of Spinal Cord Medicinementioning
confidence: 99%
“…34 Furthermore, EMS was suggested to be less effective than electrical stimulation cycling on BMD prevention after SCI. 20 The present protocol used stimulation patterns that acutely decrease the serum concentration of osteoclastic markers in men with recent SCI (i.e. CTx), 24 suggesting a positive effect on bone metabolism.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Dolbow et al (29) illustrated that rehabilitation exercise interventions that provide enough stress are suitable for improving BMD. Some studies showed that functional electrical stimulation-cycling did not have significant effects on bone loss after SCI (30)(31)(32), But others illustrated that regular long-term FES cycle exercise can reverse loss of bone mass in SCI (26, 33).…”
Section: Discussionmentioning
confidence: 99%
“…Treatments such as electrical stimulation or medications to prevent low bone mass or osteoporosis in pediatric spinal cord injury have remained elusive. A comparative study of functional electrical stimulation (FES) cycling vs passive cycling vs electrical stimulation for 60 min a day, 3 days per week for 6 months did not reveal any differences in bone mineral density in the femur, hip or tibia either between or within groups over the course of the study [26]. In a sample of 82 children with spinal cord injury, 40 % had vitamin D insufficiency and 39 % had vitamin D deficiency [20].…”
Section: Autonomic Dysreflexiamentioning
confidence: 99%